A Study On Clinical and Laboratory Profile of Children with COVID-19 Attending A Tertiary Care Hospital in Bangladesh (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: An outbreak of COVID-19 caused by 2019 novel coronavirus started first in Wuhan, Hubei province of China. Thereafter it spreaded to different countries of the world. Cases among children has been increasing day by day. Despite taking all measures of prevention virus spreading is uncontrolled.Objectives: To determine the clinical features and laboratory profile of children with COVID-19.Methods: This was a cross sectional study conducted in Dr. MR Khan Shishu Hospital and Institute of Child Health, Dhaka. Clinical and laboratory profile were analyzed among the children (aged 0-16 years) admitted between 1st May 2020 to November 2020 with positive RT-PCR for COVID-19. Data were analyzed by using SPSS.Results: Total 159 cases were included in the study. The most common symptom was fever (97.5%), then the second most common was cough (80.5%), other symptoms were diarrhea (28.3%), vomiting (17%), anorexia (30.8%) and weakness (30.2%). WBC count was within normal limit, leucocytosis was found in 5% cases and leucopenia in 3% cases. Few cases were reported with neutropenia and lymphopenia. Few cases were reported as thrombocytosis. ESR and CRP were high. Chest X-ray showed opacities in 62.9% cases. In most of the cases it was bilateral, few cases showed unilateral. In 37.1% cases it was normal. The disease category of all infected children remained same all through the hospital stay and no mortality was seen.Conclusion: Children with COVID-19 had distinct clinical features. Fever and cough were the most common symptoms. WBC count was found within normal limit but ESR and CRP were high. Chest radiograph showed opacities in majority cases. The outcome of COVID-19 in children was good.DS (Child) H J 2020; 36(2): 95-100